2007
DOI: 10.1007/s00586-007-0511-y
|View full text |Cite
|
Sign up to set email alerts
|

Predictive validity of initial fear avoidance beliefs in patients with low back pain receiving physical therapy: is the FABQ a useful screening tool for identifying patients at risk for a poor recovery?

Abstract: Several prospective studies examining patients receiving physical therapy support the predictive validity of FABQ subscale scores. This has lead to the proposition that the FABQ would be a useful screening tool, permitting early identification of patients at risk for a poor outcome with an opportunity to modify the treatment accordingly. However, the predictive validity of the FABQ within physical therapy practice has yet to be examined. Predictive validity was analyzed between the FABQ-PA, FABQ-W using both d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 47 publications
2
40
2
Order By: Relevance
“…These findings are in contrast to those of other studies in physical therapy settings, in which higher fear-avoidance scores predicted poorer outcomes. 8,11 These results are, however, similar to those of a cohort study which found that initial FABQ-PA score levels were not predictive of discharge pain or disability in patients with low back pain, 4 and to those of a randomized trial which reported better treatment outcomes for participants with elevated fear-avoidance beliefs who received graded exercise. 10 In the current study, the elevated fear-avoidance group was not put into a specific treatment group but received a patient-centered plan of care tailored towards their elevated fearavoidance beliefs.…”
Section: Discussionsupporting
confidence: 68%
“…These findings are in contrast to those of other studies in physical therapy settings, in which higher fear-avoidance scores predicted poorer outcomes. 8,11 These results are, however, similar to those of a cohort study which found that initial FABQ-PA score levels were not predictive of discharge pain or disability in patients with low back pain, 4 and to those of a randomized trial which reported better treatment outcomes for participants with elevated fear-avoidance beliefs who received graded exercise. 10 In the current study, the elevated fear-avoidance group was not put into a specific treatment group but received a patient-centered plan of care tailored towards their elevated fearavoidance beliefs.…”
Section: Discussionsupporting
confidence: 68%
“…Previous studies have tested the predictive validity of questionnaires using a variety of methods [19,20]. In the current study, the predictive validity and external validity of the SBT met the criteria proposed by Justice et al [10] for comparing cohorts across countries and at a different outcome time points than from that previously studied (in our case, 3 months in the current study and 6 months in the original SBT study in the UK).…”
Section: Discussionmentioning
confidence: 63%
“…Some may consider this a weakness of the current study, as fear of work activities is associated with FS outcomes in other studies 4,11,12,14,16,36,68 and can be screened efficiently. 29 However, the effect of type of payer on fear-avoidance beliefs of work items has not been studied.…”
Section: Discussionmentioning
confidence: 98%
“…There is evidence that identifying patients with elevated fearavoidance beliefs and managing them accordingly may reduce fear and improve outcomes. [3][4][5][10][11][12][13][14][15][16][17][18][19][20]36,40,41,56,68 The purpose of this study was to determine the effect of adding a single-item screening variable that classified patients with elevated versus not elevated fearavoidance beliefs of physical activities on a model that predicts risk-adjusted FS outcomes.…”
Section: T T Conclusionmentioning
confidence: 99%